Distributed Computing, Artificial Intelligence, Bioinformatics, Soft Computing, and Ambient Assisted Living 10th International Work-Conference on Artificial Neural Networks, IWANN 2009 Workshops, Salamanca, Spain, June 10-12, 2009. Proceedings, Part II - Omatu, Sigeru; Rocha, Miguel P.; Bravo, Jose; Fdez Riverola, Florentino; Corchado, Emilio; Bustillo, Andrés; Corchado Rodríguez, Juan Manuel (Theoretical Computer Science and General Issues,, 2009)
This book constitutes the refereed proceedings of the 10th International Work-Conference on Artificial Neural Networks, IWANN 2009, held in Salamanca, Spain in June 2009. The 167 revised full papers presented together with 3 invited lectures were carefully reviewed and selected from over 230 submissions. The papers are organized in thematic sections on theoretical foundations and models; learning and adaptation; self-organizing networks, methods and applications; fuzzy systems; evolutionary computation and genetic algoritms; pattern recognition; formal languages in linguistics; agents and multi-agent on intelligent systems; brain-computer interfaces (bci); multiobjetive optimization; robotics; bioinformatics; biomedical applications; ambient assisted living (aal) and ambient intelligence (ai); other applications.